Penerapan Misi Kristen oleh Badan Christian Veterinary Mission (CVM) terhadap Pengembangan Pertanian/Peternakan dan Pendidikan bagi Masyarakat (International Forum of Researchers and Lecturers, 2025)
This study aims to describe the implementation of the Christian mission by the Christian Veterinary Mission (CVM) in the development of agriculture/livestock and education for students of IAKN Tarutung, which also focuses on evangelism that introduces Christ to the communities and students being served. CVM, as an international Christian mission organization, carries out services that combine spiritual and practical approaches, particularly among communities that also include IAKN Tarutung students, through technical assistance, training, community empowerment, and educational support. This research uses a qualitative research method with a descriptive analysis approach, utilizing data collection techniques through in-depth interviews, observations, and documentation from CVM workers, scholarship recipients, and the communities involved in the program. The theoretical basis of this research refers to the thoughts of David J. Bosch, who asserts that mission is an attribute of God (missio Dei) and the church is merely an instrument sent to carry it out. This also underpins the view that CVM's mission is not merely evangelism, but also practical service that addresses the real needs of society. The research findings indicate that CVM implements a holistic mission that focuses not only on evangelism but also on economic empowerment through agricultural and livestock training, improving the quality of human resources through formal and non-formal education, and building social and spiritual relationships within the community. This research emphasizes that CVM's application of the Christian mission is capable of providing positive transformation that encompasses social, economic, educational, and spiritual aspects of the community. This finding is expected to serve as a reference for the development of Christian mission models in other regions with relevant and contextual approaches.